Perkembangan Psikologi: Kelahiran Integral ? - Effendy, Nurlaila (Faculty of Psychology, Universitas Surabaya, 2009)
The purpose of this study was to revisit the essence of psychology as a science. Through a literature review it was obvious that psychology as a science has the potential to be fragmented or in- tegrated. The optimism that psychology can be integrated has risen after the discussion of integration in psychology by Evolutionary Psychology, Knowledge Tree System, and Integral Psychology. Inte- gral Psychology focuses at all levels and quadrants such as upper left quadrant as individual cons- ciousness that also connected to collective consciousness in lower left quadrant, and empirical obser- vation in both the upper and lower right quadrant. Therefore the discussion in Integral Psychology involves all levels and all quadrants. Integral is an integration which contains all aspects of human being in all quadrants and levels. Psychological studies as a whole will show and support that psycho- logy is a science because it is integrated. Perkembangan ilmu psikologi mempunyai potensi menjadi terfragmentasi atau terintegrasi. Optimisme bahwa ilmu psikologi dapat terintegrasi muncul setelah pembahasan integrasi pada ilmu psikologi oleh Psikologi Evolusioner, Sistem Pohon Pengetahuan, dan Psikologi Integral. Fokus Psikologi Integral pada kuadran kiri atas sebagai kesadaran individual, namun individu terkait kesadaran kolektif pada kuadran kiri bawah dan observasi empiris pada kuadran kanan atas maupun kanan bawah, sehingga pembahasan psikologi integral meliputi semua kuadran dan semua aras (level). Integral adalah integrasi yang meliputi semua aspek diri manusia dalam semua kuadran dan semua aras. Kajian psikologi sebagai kesatuan akan mendukung bahwa psikologi adalah ilmu karena terintegrasi.